Generic phylogeny and character evolution in Urticeae (Urticaceae) inferred from nuclear and plastid DNA regions. Issue 1 (9th February 2015) - Kim, Changkyun; Deng, Tao; Chase, Mark; Zhang, Dai-Gui; Nie, Ze-Long; Sun, Hang
Abstract: This study examines phylogenetic relationships among the 12 genera of Urticeae (Urticaceae) and investigates the pattern of morphological evolution based on analysis of nuclear ribosomal internal transcribed spacer (nrITS) and two plastid DNA regions ( rbcL exon, trnL ‐ F spacer). Sequence data were analyzed using maximum parsimony and Bayesian inference, and selected morphological traits were mapped onto the molecular tree. The molecular results strongly supported monophyly of Urticeae, excluding Gyrotaenia, which is related to Elatostemateae. All genera were monophyletic except for Urtica, Laportea, and Urera . Two Hesperocnide species are nested within Urtica . Laportea and Urera are divided into three groups with a strong geographical signal. The inferred phylogeny indicates five well‐supported clades in Urticeae: clade A including Urtica (with Hesperocnide ), Zhengyia, Laportea I, and Nanocnide ; clade B comprising Dendrocnide and Discocnide ; clade C including only Girardinia ; clade D including Laportea II; and clade E including Obetia, Urera I, II, III, and Poikilospermum . Although it is difficult to identify morphological synapomorphies for these well‐defined clades within Urticeae, character analysis shows that the herbaceous habit and alternate leaves are the ancestral states in the tribe. The presence of stinging hairs is the derived status in Urticeae, and it might have been a key innovation triggering species diversification in the tribe.